Introduction to burnout and well-being for anesthesiologists in South Korea: narrative and brief review - Jeongrim Lee (Anesthesia and Pain Medicine, 2025)
Burnout is a widespread occupational issue in the medical field, posing significant risks to both physician health and patient care worldwide. While the COVID-19 pandemic highlighted the impact of systemic factors—such as excessive workloads, administrative burdens, and inefficiencies—in exacerbating physician burnout, discussions about well-being remain limited in South Korea. Given the recent challenges faced by healthcare professionals in Korea, addressing burnout has become urgent to prevent further negative outcomes. Although individual efforts toward wellness are important, they are insufficient without systemic support. Distinguishing between burnout and well-being is crucial for developing targeted interventions. Drawing on global examples, comprehensive strategies—including policy reforms, organizational support, mental health resources, and cultural shifts—are recommended to create a sustainable and supportive environment for anesthesiologists in Korea.